When Assessment Becomes Learning: Collaborative Assessment and Self-Reflection in EFL Writing Classes - Tintin Susilowati; Ana Maghfiroh; Aries Fachriza (Universitas Hamzanwadi, 2026)
Writing remains a demanding skill for EFL students because it requires coordinating idea development, linguistic accuracy, organization, revision, and evaluative judgment. This study explored students’ perceptions of the integrated use of Collaborative Assessment (CA) and Self-Reflection (SR) in supporting writing development. Using a qualitative exploratory case study design, the research involved 51 English Education Department students from three writing classes at a State Islamic University in Indonesia. Data were collected through CA and SR questionnaires administered after six meetings of writing instruction incorporating collaborative assessment and reflective activities, followed by semi-structured interviews to obtain deeper insights into students’ experiences. The data were analyzed using thematic and interactive analysis involving data condensation, data display, conclusion drawing, and verification. The findings indicate that students perceived CA and SR as complementary learning-oriented assessment practices. CA supported writing development by enabling students to discuss drafts, exchange feedback, identify writing problems, learn from peers, and receive lecturer guidance during assessment. SR strengthened this process by helping students recognize past mistakes, understand the purposes of their writing, plan their ideas, monitor their language use, and identify areas for improvement. Together, CA and SR transformed assessment from a product-oriented judgment into an interactive and reflective learning process. These findings suggest that EFL writing instruction should integrate collaborative feedback cycles with structured self-reflection to help students move from receiving feedback to using it critically for revision, self-awareness, and continuous improvement in writing.